OVERPRESSURE CHARACTERISTICS IN THE LANGKAT FIELD, NORTH SUMATRA BASIN - HERMAWAN YOSANDIAN (NIM : 12009008) ; Pembimbing : Prof. Ir. Lambok M. Hutasoit, Ph.D., HAZMANU
Overpressure zone has long been recognized to be present in Baong Formation, North Sumatra Basin, specifically at the Langkat Field. However, overpressure characteristics in the area are poorly understood. The characteristics include overpressure pattern and distribution, and also its generating mechanism. The purpose of this research is to address such characteristics at the Langkat Field. The data used in this research are wireline log, pressure, and drilling report from four wells belonging to PT. Pertamina. The overpressure occurence is detected from sonic log deflection, meanwhile overpressure generating mechanism is analyzed from wireline log profiles, confirmed by DuttaÃ‚Â’s crossplot, geothermal gradient, and richness and maturation of source rock. This research concludes that overpressure zone in the research area is detected at Lower Keutapang and Baong formations. Pore pressure predictions show that overpressure is increasing in shale-dominant sequence and decreasing in shale-sand intercalation sequence. Meanwhile, overpressure generating mechanisms of the research area are loading and non-loading mechanisms. The loading mechanism is detected at Gohor Lama-1, while at the other three wells, the overpressure is generated by non-loading mechanism. The non-loading mechanism is caused by clay diagenesis and hydrocarbon generation.